Father Ed : the story of Bill W.'s spiritual sponsor - Goldstein, Dawn Eden, 1968- (Orbis Books, 2022)
"A biography of Father Edward Dowling, SJ, a Jesuit priest who served as a spiritual counselor to Bill W., founder of Alcoholics Anonymous"--